Filamentation Is Associated with Reduced Pathogenicity of Multiple Non-albicans Candida Species - Mohua Banerjee (American Society for Microbiology, 2019)
ABSTRACT Candidiasis affects a wide variety of immunocompromised and medically compromised patients. Candida albicans, a major human fungal pathogen, accounts for about 50% of all cases, while the remainder are caused by the less pathogenic non-albicans Candida species (NACS). These species are believed to be less pathogenic, in part, because they do not filament as readily or robustly as C. albicans, although definitive evidence is lacking. To address this question, we used strains for two NACS, Candida tropicalis and Candida parapsilosis, which were genetically engineered to constitutively express the key transcriptional regulator UME6 and drive strong filamentation both in vitro and during infection in vivo. Unexpectedly, both strains showed a dramatic reduction in organ fungal burden in response to UME6 expression. Consistent with these findings, we observed that a C. tropicalis hyperfilamentous mutant was significantly reduced and a filamentation-defective mutant was slightly increased for organ fungal burden. Comprehensive immune profiling generally did not reveal any significant changes in the host response to UME6 expression in the NACS that could explain the increased clearance of infection. Interestingly, whole-genome transcriptional profiling indicated that while genes important for filamentation were induced by UME6 expression in C. tropicalis and C. parapsilosis, other genes involved in a variety of processes important for pathogenesis were strongly downregulated. These findings suggest that there are fundamental evolutionary differences in the relationship between morphology and pathogenicity among Candida species and that NACS do not necessarily possess the same virulence properties as C. albicans. IMPORTANCE Many immunocompromised individuals, including HIV/AIDS and cancer patients, are susceptible to candidiasis. About half of all cases are caused by the major fungal pathogen Candida albicans, whereas the remainder are due to less pathogenic non-albicans Candida species (NACS). Generation of filamentous cells represents a major virulence property of C. albicans, and the NACS are believed to be less pathogenic, in part, because they do not filament as well as C. albicans does. To address this question, we determined the pathogenicity of two NACS strains that have been genetically engineered to promote filamentation during infection. Surprisingly, these strains showed a dramatic reduction in pathogenicity. The host immune response did not appear to be affected. However, unlike C. albicans, filamentation of the NACS was associated with downregulation of several genes important for pathogenicity processes. Our results suggest that there are fundamental evolutionary differences in the relationship between filamentation and pathogenesis in NACS compared to C. albicans.